Clinical and radiological evaluation of osteoarthritis in knee pain patients and its association with inflammatory markers at MGM Medical College Hospital, Jamshedpur - Abhishek Guria; Vibhas Chandra; Bhaskar Bej; Kumar Vimal; Rajan K. Barnwal; Uma S. Singh; Kuber C. Setua (Journal of Family Medicine and Primary Care)
Context: Knee osteoarthritis, a global joint disorder, affects 22%–39% of the population, with a higher incidence in India among women aged 65 and above. Biochemical markers like cytokines could help detect and treat the disease, potentially reducing socioeconomic costs and enabling a transition from degenerative to mechanical stress-induced disease. Aims: To investigate the epidemiology of osteoarthritis in knee pain in adults, its clinical and radiological evaluation, and its association with inflammatory markers. Settings and Design: The Department of Orthopaedics at MGMMCH, Jamshedpur, conducted this cross-sectional study. Methods and Material: The study analyzed 170 patients with knee OA symptoms from August 2023 to February 2024, using the KOOS Knee Survey clinical criteria. We used the Kellgren and Lawrence scale for radiological diagnosis of knee osteoarthritis. Statistical Analysis Used: The study utilized descriptive statistics, Chi-square test, and bivariate Spearman’s correlation, with statistical significance determined by P values of <0.05. Results: We found that the overall prevalence of knee Osteoarthritis was 70%. We discovered that 59.4% of us were male. The majority were aged 40–49 (32%), 50–59 (25.3%), and 30–39 (14.1%). The grade of knee pain showed a statistically significant strong positive correlation (P = 0.000) between age, Body mass index, C-reactive protein, Rheumatoid factor, Interleukin-6, Interleukin 1β, and TNFα. Conclusions: Knee osteoarthritis is prevalent in younger individuals, with males more affected. Elevated IL6, IL1β, and TNFα levels in meniscectomy patients increase osteoarthritis risk, potentially aiding targeted treatment.